Strategi Pembelajaran Tahfidz Al-Qur’an di Lembaga Pendidikan - Hidayah, Nurul (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
Antusisame world Islamic education in carrying Tahfidz Quran needs to get a positive response and a serious concern, especially related strategies to develop it. This is because there are still some difficulties were experienced by some Islamic educational institutions, among others: poor management of Tahfidz, less active role of the teacher / instructor Tahfidz in guiding and motivating students penghafal Koran, mechanisms and methods applied by teachers Tahfidz , lack of parental support, and lack of control and motivation superiors. To overcome these weaknesses is necessary strategies include: mamanej Tahfidz well, activating the role of teachers and motivate students Tahfidz, perfecting mechanisms and methods Tahfidz, optimize parental support, and optimize control and motivation superiors.